g+3/2=3

Simple and best practice solution for g+3/2=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+3/2=3 equation:



g+3/2=3
We move all terms to the left:
g+3/2-(3)=0
determiningTheFunctionDomain g-3+3/2=0
We multiply all the terms by the denominator
g*2+3-3*2=0
We add all the numbers together, and all the variables
g*2-3=0
Wy multiply elements
2g-3=0
We move all terms containing g to the left, all other terms to the right
2g=3
g=3/2
g=1+1/2

See similar equations:

| -6n+1+4=-4n-3 | | -6a+3+7a=12-22 | | 15=3(2x-5) | | 7-x/5=-2 | | -5n-2=35 | | b/8b+5=29 | | h+3(3h+4)=-8 | | -4f+11=8-4f+1 | | 3=d3 | | -7-3x=15 | | (4x-3)/5=(2x+11)/3 | | 3x-130=2x | | 50000=x+(x*0.0625) | | 7u-4=-11 | | 23=-4r | | 8x+99+8x+99=9x+170 | | 78+64+7x+3=180 | | 7(-x/5)=-2 | | 4(3x+8)=10x+2x+32 | | 33+114+3a=180 | | -3x+8x-67=78 | | 3x-19=61 | | 2x+1(2x-17)=86 | | 2x+15=3x+15=180 | | -4a+2=6a+12 | | m1°=21,m2° | | 82-0.4x=82 | | 2(n-4)=-3n-12 | | 4/z-1=8/6 | | x-6=40=-8(x+8) | | 111=3(1-5x)+3 | | 7/9x-23=33 |

Equations solver categories